PENGARUH SIZE, LEVERAGE, PROFITABILITY, CAPITAL INTENSITY RATIO DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE (ETR) (Studi Kasus Perusahaan Wholesale And Retail Trade Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) (Students' Journal of Accounting and Banking, 2015)
This study is done to analyse the variable of size, leverage, profitability (ROA), capital intensity ratio, and independent commissioner on the effective tax rate. The object of this study are companies wholesale and retail trade enrolled in the indonesia stock exchange BEI (2012-2014) year. Effective tax rate (ETR) is a the ratio of a tax paid for pretax profit at a specified period of . ETR also used for measuring a tax paid as a proportion of economic income. The purpose of this research is to test the influence of size, leverage, profitability (ROA), capital intensity ratio (CIR), and independent commissioner that is the measurement of effective tax rate. The population of this study are companies wholesale and retail trade years of successive 2012-2014 registered in indonesia stock exchange (BEI). The technique of the purposive sampling sample collection and use of successive data company received a sample of 53. The company then tested with normality, multikolinieritas, autokorelasi, and heteroskedastisitas. Next researchers used regression double to know the relationship between the variables. This research result indicates that variable size significant negative effect on ETR. Leverage influential no significant on ETR. Profitability (ROA) have no significant on ETR. Capital intensity ratio have positive effects and against significant ETR. Independent commissioner have no significant on ETR.Keywords: Size, Leverage, Profitability, Capital Intensity The Ratio, Independent Commissioner and Effective Tax Rate